Addition of sodium metabisulphite to left atrial catheter infusates as a means of preventing bacterial colonisation of the catheter tip. Issue 2 (February 1982) - Freeman, R; Holden, M P; Lyon, R; Hjersing, N
Abstract : Sodium metabisulphite (SMBS) was added at a concentration of 0.05% to the dextrose-heparin solution used to flush left atrial catheters in one group of open-heart surgery patients. Two other groups of patients had left atrial catheters flushed with dextrose-heparin alone. Comparison of the isolation rate of organisms from the tips of the catheters in the three groups showed that the addition of SMBS significantly reduced bacterial contamination in the lines (two isolations from 36 catheters with SMBS added, compared with 13 from 56 and 15 from 65 in the other groups–that is, 5.55% compared with 23.2% and 23.1%). The protective effect of the SMBS was particularly evident in the first 48 hours after catheter insertion. No haematological or biochemical insult was found.